2009
DOI: 10.4315/0362-028x-72.7.1491
|View full text |Cite
|
Sign up to set email alerts
|

Specific PCR Detection of Arcobacter butzleri, Arcobacter cryaerophilus, Arcobacter skirrowii, and Arcobacter cibarius in Chicken Meat

Abstract: An enrichment PCR assay using species-specific primers was developed for the detection of Arcobacter butzleri, Arcobacter cryaerophilus, Arcobacter skirrowii, and Arcobacter cibarius in chicken meat. Primers for A. cryaerophilus, A. skirrowii, and A. cibarius were designed based on the gyrA gene to amplify nucleic acid fragments of 212, 257, and 145 bp, respectively. The A. butzleri-specific primers were designed flanking a 203-bp DNA fragment in the 16S rRNA gene. The specificity of the four primer pairs was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…Studies on foods have shown that, in general, A. butzleri is the most prevalent species, followed by A. cryaerophilus and A. skirrowii, as reviewed by Lehner et al (101) and further demonstrated in other recent studies (25,125,135). This has probably been the reason for the inclusion of Arcobacter butzleri in the list of microbes considered a serious hazard to human health by the International Commission on Microbiological Specifications for Foods (81).…”
Section: Arcobacter In Foodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Studies on foods have shown that, in general, A. butzleri is the most prevalent species, followed by A. cryaerophilus and A. skirrowii, as reviewed by Lehner et al (101) and further demonstrated in other recent studies (25,125,135). This has probably been the reason for the inclusion of Arcobacter butzleri in the list of microbes considered a serious hazard to human health by the International Commission on Microbiological Specifications for Foods (81).…”
Section: Arcobacter In Foodsmentioning
confidence: 93%
“…However, it should be taken into consideration that more than one Arcobacter sp. can normally be isolated in food products (25,71,125,155). Less commonly isolated species are A. nitrofigilis (25,107) and A. mytili and A. thereius (25).…”
Section: Arcobacter In Foodsmentioning
confidence: 99%
“…Authors reported that mPCR of Houf et al (2000) was most commonly referred followed by Figueras et al (2008) which employed 16S rDNA-RFLP and then m-PCR of Douidah et al (2010). However, Levican and Figueras (2013) found that none of the five PCR developed by different authors (Houf et al 2000;Kabeyaet al 2003a;Figueras et al 2008;Pentimalli et al 2009;Douidah et al 2010) were reliable. Authors concluded that result was bad for identification of A. cryaerophilus and A. butzleri using 23S rRNA gene as the target (Levican & Figueras 2013).…”
Section: Detection Of Arcobacter Spp By Molecular Methodsmentioning
confidence: 99%
“…. Pentimalli et al (2009) developed a PCR assay using species-specific primers for the detection of A. butzleri, A. cryaerophilus, A. skirrowii and A. cibarius in chicken meat. A multiplex-PCR assay with seven primers was developed by Douidah et al (2010) for the identification of the five human and mammal related species of Arcobacter (A. butzleri, A. cryaerophilus, A. skirrowii, A. thereius and A. cibarius).…”
Section: Detection Of Arcobacter Spp By Molecular Methodsmentioning
confidence: 99%
“…González et al (2014) developed an Arcobacter genus-specific PCR assay designed to amplify an 85 bp DNA fragment on the 16S rRNA gene. A PCR assay using species-specific primers has been developed for the detection of A. butzleri, A. cryaerophilus, A. skirrowii, and A. cibarius in chicken meat (Pentimalli et al 2009). Levican and Figueras (2013) compared the performance of five PCR methods that target regions of 16S rRNA, 23S rRNA, or gyrA genes to identify Arcobacter species.…”
Section: Isolation and Identificationmentioning
confidence: 99%